#Blackgirlsmatter: Turning the Tide of Historical Injustice toward Civil and Social Restitution. Issue 5 (18th September 2020) - Dorsey, Marquitta S.
ABSTRACT: Historical trajectories of explicit disregard contribute to current day biases related to the health and well-being of Black women and girls. In the current study, a multi-faceted analysis is used to examine linkages between historical mistreatment, twenty-first-century health disparities and specific problems with quality of care, access to resources and a lack of regard for the personal agency of Black women and girls. Considering systemic biases, the author asserts six core components of intersectionality to guide six practical solutions for reducing sexual health disparities experienced by Black women and girls in America.